Iraqi University Students’ Exposure to Digital Journalism and Their Realized Satisfactions: A Field Study on Baghdad University Students - Aziz, Ass.Lec Issa jassim (Thi Qar Arts Journal, 2024)
The world is witnessing rapid developments in the field of communication, significantly impacting digital media, which combines information technology and communication technology. This convergence has given rise to a genuine market for multimedia, allowing the integration of diverse data from various sources, including text, images, audio, data, graphics, and videos. Consequently, new forms of interactive multimedia products have emerged, encouraging users to engage with them. Previously, user engagement was limited to traditional media. However, users now seek better spaces for expression and communication. This transformation has led to new media patterns.Communication channels have undergone several revolutions, each leaving distinct imprints on society. Among these, the most influential has been the fusion of communication channels. This fusion enables the dissemination, collection, storage, retrieval, and rapid transmission of vast amounts of information and data to users worldwide. It has broken down geographical barriers between countries and continents, increasing the impact of events occurring in other nations.